Research on Marine Environmental Noise Based on Acoustic Bait Domestication Technology - Chen, Shuai; Huang, Hongliang; Li, Lingzhi; Rao, Xin; Zhang, Yuqing (International Journal of Natural Resources and Environmental Studies, 2024)
Acoustic domestication type of marine pastures are generally established in shallow waters with water depth not exceeding 200 m. In order to study the effect of acoustic domestication, this paper aims to investigate the environmental noise in the shallow waters of the sea. Unlike the stable deep sea environment, the environmental noise in the shallow sea is extremely complex, which has a direct impact on the effect of acoustic domestication. In this paper, in order to study the marine environmental noise, a hydroacoustic signal processing system is established, which is divided into two parts: the hardware part and the software part; the hardware part is mainly for signal sampling, and the software part is for signal processing. The hardware part of the hydroacoustic signal processing system includes three parts: acoustic-electric conversion, intermediate processing and signal recording. The study of ship noise showed that the fishing boat is about 5m long, with a power of 60hp, and passes about 10m away from the hydrophone, and it is more than 10dB higher than that without a ship, when there is a ship passing, in which the 400Hz is 17.82dB higher. Measurements of ocean ambient noise at different depths show that the noise decreases with depth, but when close to the seabed, the noise decreases with depth due to the reflection effect of the seabed on the sound and the biological noise of the seabed.